Effect of Biosynthesized Silver Nanoparticles on Bacterial Biofilm Changes in S. aureus and E. coli - Hosnedlova, Bozena; Kabanov, Daniil; Kepinska, Marta; B Narayanan, Vedha Hari; Parikesit, Arli Aditya; Fernandez, Carlos; Bjørklund, Geir; Nguyen, Hoai Viet; Farid, Awais; Sochor, Jiri; Pholosi, Agnes; Baron, Mojmir; et al. (Nanomaterials, 2022)
One approach for solving the problem of antibiotic resistance and bacterial persistence in biofilms is treatment with metals, including silver in the form of silver nanoparticles (AgNPs). Green synthesis is an environmentally friendly method to synthesize nanoparticles with a broad spectrum of unique properties that depend on the plant extracts used. AgNPs with antibacterial and antibiofilm effects were obtained using green synthesis from plant extracts of Lagerstroemia indica (AgNPs_LI), Alstonia scholaris (AgNPs_AS), and Aglaonema multifolium (AgNPs_AM). Nanoparticles were characterized by transmission electron microscopy (TEM) and energy-dispersive X-ray spectroscopy (EDX) analysis. The ability to quench free radicals and total phenolic content in solution were also evaluated. The antibacterial activity of AgNPs was studied by growth curves as well as using a diffusion test on agar medium plates to determine minimal inhibitory concentrations (MICs). The effect of AgNPs on bacterial biofilms was evaluated by crystal violet (CV) staining. Average minimum inhibitory concentrations of AgNPs_LI, AgNPs_AS, AgNPs_AM were 15 ± 5, 20 + 5, 20 + 5 μg/mL and 20 ± 5, 15 + 5, 15 + 5 μg/mL against Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria, respectively. The E. coli strain formed biofilms in the presence of AgNPs, a less dense biofilm than the S. aureus strain. The highest inhibitory and destructive effect on biofilms was exhibited by AgNPs prepared using an extract from L. indica.